Economic Evaluation of Species Composition Effects on Feed Costs in Indi an Major Carp Polyculture: A Case Study from Tripura, India (Indian Journal of Animal Production and Management, 2025)
In this study, the ratio of feed cost to production income was determined for carp  polyculture systems in Tripura, India. Data was collected from experimental ponds  over a 10-month culture period from May to February. Three different species  compositions of Indian major carps were evaluated: Treatment 1 (Catla 40%, Rohu  30%, Mrigal 30%), Treatment 2 (Catla 30%, Rohu 40%, Mrigal 30%), and Treatment  3 (Catla 30%, Rohu 30%, Mrigal 40%). All ponds were stocked at a density of 7500  fingerlings per hectare in 200 m² experimental ponds with water depths of 1-1.5  m. Feed consumption, growth parameters, and economic indicators were monitored  throughout the production cycle. Other operating costs during the production  period (pond preparation, fingerlings, labor, equipment, depreciation, marketing,  etc.) were excluded from the analysis. In carp polyculture, feed represents the highest  share of total production costs during the growing period. According to the study  results, the feed cost/production income ratio of Treatment 2 was the most favorable  at 0.28, followed by Treatment 1 at 0.29, and Treatment 3 at 0.31. Production  levels ranged from 4000-4090 kg/ha across treatments. Treatment 2 showed better  economic performance due to the higher proportion of Rohu, which demonstrated  superior feed conversion rates under the study conditions. The findings suggest that  optimizing species composition in carp polyculture systems can improve economic  returns by enhancing feed utilization efficiency.
Keywords: Composite fish culture; Indian major carps; Feed Cost; Production Income; NE India